Cochrane Database of Systematic Reviews 2000
DOI: 10.1002/14651858.cd002229
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy for preventing cardiovascular disease in post-menopausal women

Abstract: Background-There is apparently compelling evidence, from observational studies, that hormone replacement therapy (HRT) may have benefits in reducing cardiovascular events in postmenopausal women. However, these observational data are subject to biases and confounding and require support from formally designed randomised controlled trials of the effects of HRT on cardiovascular disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…21 In the present study, reduced GFR was associated with a high risk of stroke in men after adjustment for demographic factors but not after adjustment for potential confounding factors; however, this relationship was still observed in women even after adjustment for confounding factors. This sex difference may be a consequence of the effects of residual confounding factors, specifically, hypercoagulable states 22 or gonadal steroids, 23 in women. Furthermore, the lack of a significant association between reduced GFR and a high risk of myocardial infarction is probably due to the relatively small number of events.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the present study, reduced GFR was associated with a high risk of stroke in men after adjustment for demographic factors but not after adjustment for potential confounding factors; however, this relationship was still observed in women even after adjustment for confounding factors. This sex difference may be a consequence of the effects of residual confounding factors, specifically, hypercoagulable states 22 or gonadal steroids, 23 in women. Furthermore, the lack of a significant association between reduced GFR and a high risk of myocardial infarction is probably due to the relatively small number of events.…”
Section: Discussionmentioning
confidence: 99%
“…These results are incongruous with most other studies, observational 2 3 as well as randomised. [18][19][20] This may be due to the differences in the administered hormones; 17-β-estradiol has been reported to be less thrombogenic than conjugated equine oestrogen. 21 22 In human aortic endothelial cells 17-β-estradiol is superior to conjugated equine oestrogen in increasing the production of nitric oxide, partially because of a higher ability to activate the production of endothelial nitric oxide synthase.…”
Section: Thromboembolismmentioning
confidence: 99%
“…However, recent studies found an increased risk of breast cancer, heart attacks and strokes in patients on HRT. [2][3][4][5] In view of this, patients increasingly access alternative, non-hormonal treatment for menopausal symptoms. 6 Anumber of reviews of the effectiveness of complementary therapies for hot flushes have been published.…”
Section: Introductionmentioning
confidence: 99%